Victimology in the adversarial accusatory criminal system (Revista de Investigaciones Universidad del Quindío, 2020)
Victimology is described as the study of the way in which a person becomes a victim, the various dimensions of victimization (primary, secondary and tertiary), and the prevention and reduction strategies, as well as the set of responses social, legal and welfare, aimed at reparation and social reintegration of the victim. Due to the aforementioned, this document provides notes regarding the complementary importance of knowing in depth this study applied to the crime duo called victim-perpetrator in knowing the victimological processes and their scope for their attention and application in view of restorative justice.
Keywords: criminology; justice system; victim